2021
DOI: 10.1016/j.exphem.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-223-3p modulates ibrutinib resistance through regulation of the CHUK/Nf-κb signaling pathway in mantle cell lymphoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…miRNAs are small (~20-22 nucleotides) noncoding regulatory RNAs that bind to a specific target mRNA through a sequence that is complementary to the 3′-UTR of the target mRNA [23]. Several miRNAs regulate oncogenic or tumorsuppressive pathways, such as the NF-κB or BCR signaling cascade in B-cell malignancies [21,22,24,25]. Our previous studies have shown aberrant regulation of miR-377 in germinal center-type DLBCL that targets BCL-xL, and thus drives acquired resistance to BCL-xL inhibition by venetoclax [23].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small (~20-22 nucleotides) noncoding regulatory RNAs that bind to a specific target mRNA through a sequence that is complementary to the 3′-UTR of the target mRNA [23]. Several miRNAs regulate oncogenic or tumorsuppressive pathways, such as the NF-κB or BCR signaling cascade in B-cell malignancies [21,22,24,25]. Our previous studies have shown aberrant regulation of miR-377 in germinal center-type DLBCL that targets BCL-xL, and thus drives acquired resistance to BCL-xL inhibition by venetoclax [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance is a major challenge resulting in cancer recurrence and an unfavorable prognosis [ 80 ]. Recent findings demonstrate that NF-κB regulates chemotherapy resistance in various tumors, including gastric cancer [ 81 , 82 ], CRC [ 83 ], NSCLC [ 84 , 85 , 86 ], pancreatic ductal adenocarcinoma (PDAC) [ 87 ], breast cancer [ 88 , 89 , 90 , 91 , 92 ], prostate cancer [ 93 ], GBM [ 94 , 95 ], and hematological tumors [ 96 , 97 , 98 , 99 ].…”
Section: Association Of Nf-κb With Therapeutic Resistancementioning
confidence: 99%
“…Mantle cell lymphoma (MCL) is a refractory aggressive lymphoma with an adverse clinical outcome. MiR-223-3p could directly inhibit conserved helix-loop-helix ubiquitous kinase (CHUK) and further decrease the expression of NF-κB, thereby reversing Bruton’s tyrosine kinase (BTK) inhibitor ibrutinib resistance in MCL [ 96 ].…”
Section: Association Of Nf-κb With Therapeutic Resistancementioning
confidence: 99%
“…The overexpression of miR-217 in COC1 cells facilitated CDDP-induced apoptosis and enhanced CDDP sensitivity by inhibiting the activation of the Wnt/b-catenin signaling pathway (146). In addition, multiple miRNAs, such as miR-323a-3p, miR-6727-5p, and miRNA-223-3p, have also been found to contribute to the development of cancer drug resistance by regulating apoptotic pathways via targeting other drug resistance-related signaling pathways, including the phosphatidylinositol 3-kinase (PI3K)/AKT, mitogen-activated protein kinase (MAPK), and nuclear factor kappa B (NF-kB) signaling pathways (147)(148)(149). Collectively, these findings indicate that targeting the apoptotic pathways is a common regulation mechanism for miRNAs in cancer drug resistance.…”
Section: Mirnas and Cancer Drug Resistance Mirnas Affect Drug-induced...mentioning
confidence: 99%